Mechanical, Thermal and Morphological Properties of Poly(lactic acid)/ Epoxidized Natural Rubber Blends - Mohd Bijarimi, Mat Piah; Sahrim, Ahmad; Rozaidi, Rasid (SAGE Publications, 2012)
In this work, we report a melt blend of poly(lactic acid)(PLA)/epoxidized natural rubber (ENR) with liquid natural rubber (LNR). The LNR was synthesized by a photochemical degradation technique and used as a compatibilizer in the PLA/rubber binary blending systems. The PLA/ENR/LNR blends were melt-blended in a Haake internal mixer at 180C and mixing speed of 50 r. min 1 for 15 min. It was found that the addition of LNR compatibilizer has improved the tensile strength and elongation at break for the compositions of the 40PLA/55ENR/5LNR blend system when compared with a noncompatibilized system (40PLA/55ENR/5NR). The elongation at break for the blend with 5% LNR compatibilizer showed a twofold increment compared with the blend without LNR. The increase in tensile strength and elongation at break were associated with the ability of LNR to promote the uniform dispersion between the natural rubber (NR) and PLA phases as observed in the scanning electron microscopic analysis. Moreover, the differential scanning calorimetric results indicated that the 40PLA/55ENR/5LNR showed the highest degree of crystallinity and thus contributed to improve their mechanical properties. Thermogravimetric analysis showed that two degradation transitions for both compatibilized and noncompatibilized blend systems due to higher degradation temperatures of ENR50 and NR parts. Fourier transform infrared spectroscopic analysis revealed that the PLA/ENR/NR and PLA/ENR/LNR blends were not miscible.